1986
DOI: 10.1097/00000658-198610000-00017
|View full text |Cite
|
Sign up to set email alerts
|

The First Open Heart Corrections of Tetralogy of Fallot

Abstract: Tetralogy of Fallot became a correctable malformation on August 31, 1954, and from that data through 1960, 106 patients (ages 4 months-45 years) who underwent open repairs at the University of Minnesota and were discharged, have been followed (99% complete) until death or for 26-31 years (mean: 23.7 years, 2424 patient years). The purposes of this study were to determine survival, morbidity, hemodynamics, educational/employment attainments, and relation of these to surgical technics. Operations were done by cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0
3

Year Published

1988
1988
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(87 citation statements)
references
References 15 publications
0
83
0
3
Order By: Relevance
“…Surgical repair of TOF has been performed since 1955. 2 Early primary repair has been recommended since the 1970s and is now routinely performed with excellent results. 3 However, we still occasionally encounter patients who have not undergone repair or have had only a palliative procedure; these patients thus are considered for surgical correction later in life.…”
Section: © 2010 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%
“…Surgical repair of TOF has been performed since 1955. 2 Early primary repair has been recommended since the 1970s and is now routinely performed with excellent results. 3 However, we still occasionally encounter patients who have not undergone repair or have had only a palliative procedure; these patients thus are considered for surgical correction later in life.…”
Section: © 2010 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%
“…Several studies from Western countries have reported the prevalence of late arrhythmias and their significance in long-term prognosis and quality of life in this patient population. [2][3][4][5][6][7][8] In Japan, Kobayashi et al reported a single institute's experience of arrhythmias analyzed by Holter monitor in postoperative TOF, 9 and recently, Niwa et al reported a Japanese survey on the quality of life in adult patients with postoperative TOF, including some data on arrhythmias. 10 These Japanese studies, however, are not comparable with the studies from Western countries in terms of the number of subjects and length of follow-up.…”
mentioning
confidence: 99%
“…4,[7][8][9][10] This report describes the longer follow-up (at least 20 years or until death) of the operative survivors of 183 patients who underwent surgical repair of isolated pulmonary stenosis. Particular attention is given to the influence, on results, of age at operation, of use of a right ventriculotomy, of right ventricular systolic pressure (before and after operation), and of the presence of a murmur of pulmonary insufficiency after operation.…”
mentioning
confidence: 99%